Tax Planning Atas Pajak Penghasilan Badan - Dheo Rimbano; Mirra Sri Wahyuni; Eri Triharyati (Politeknik Ganesha Medan, 2019)
Corporate income tax is a mandatory thing to pay. awareness of paying is still minimal, Islam is more familiar with the term ‘zakat’ than tax (Awareness in paying zakat is very high for Muslims), raising awareness begins with the planning process, so the obstacles in every plan to pay taxes need to be known. The possibility of taxpayers already knowing their obligations, but the meaning is like